2014
DOI: 10.4100/jhse.2014.91.06
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between speed factors and agility in sport games

Abstract: Horička, P., Hianik, J., & Šimonek, J. (2014). The relationship between speed factors and agility in sport games. J. Hum. Sport Exerc., 9(1),. This study deals with the issue of various understanding of the term "agility", mainly within the context of team sport games. Under this term complex psychomotor abilities are understood. Their development requires a high degree of neuro-muscular specificity. The development of these abilities are underpinned also by perceptual components including also anticipation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 12 publications
2
19
0
11
Order By: Relevance
“…When interpreting the research results we draw from the assumption that the leve l of examined speed abilities and agility in players of four selected sport games will not significantly differ with regard to the similar character of movement of players (Horička, Hianik & Šimonek, 2014). From the point of view of comparison of players in the examined sport games we found the following facts.…”
Section: Resultsmentioning
confidence: 95%
“…When interpreting the research results we draw from the assumption that the leve l of examined speed abilities and agility in players of four selected sport games will not significantly differ with regard to the similar character of movement of players (Horička, Hianik & Šimonek, 2014). From the point of view of comparison of players in the examined sport games we found the following facts.…”
Section: Resultsmentioning
confidence: 95%
“…Maka dari itu kemampuan untuk merespon stimulus dengan cepat sangat dibutuhkan untuk meningkatkan performa dalam keterampilan menggiring bola basket. The other concept represents agility development with relatively open skills, where fast changes of direction of movement are executed in training conditions, which are not structured so much and therefore are similar to the match conditions (Horička, 2014).…”
Section: Uji Hipotesis Dengan Membandingkan Nilai T-hitung Dengan T-tmentioning
confidence: 99%
“…Agility is a complex psychomotor concept which includes both neuromuscular and cognitive components such as stimulus recognition and reaction, or execution of a response (Horička, Hianik, & Šimonek, 2014;Sheppard & Young, 2014). Agility typically involves considerable spatial or temporal uncertainty while initiating whole body movement with multi-directional changes, and rapid acceleration and deceleration (Sheppard & Young, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The movement patterns are relatively closed and stereotyped, which implies that ladder drills in isolation will not necessarily address all components of agility. Other approaches to agility training include functional training in open environments, which can challenge both the perceptual and decision-making aspects of agility (Bloomfield, Polman, O'Donoghue, & Mcnaughton, 2007;Brughelli, Cronin, Levin, & Chaouachi, 2008;Horička et al 2014;Robinson & Owens, 2004;Serpell, Young, & Ford, 2011). For example, a training programme whereby athletes react to video recordings of rugby players executing specific movements, showed that the perceptual and decision-making aspects of agility were trainable (Serpell, Young, & Ford, 2011).…”
Section: Introductionmentioning
confidence: 99%